Housing‐related delayed discharge from inpatient mental health units: Magnitude and contributors in a metropolitan mental health service. Issue 1 (6th January 2021) - Nguyen, Jenny; Honey, Anne; Arblaster, Karen; Heard, Rob
Abstract: International research indicates that delayed discharges from inpatient mental health units are common and most occur because patients lack suitable housing. However, little is known about this issue in an Australian setting. This mixed‐methods study aimed to investigate the extent, cost and contributors to housing‐related delayed discharge (HRDD) from inpatient mental health units in one Local Health District in New South Wales, Australia. A medical records review was conducted to quantify housing‐related delay and housing difficulties noted. Perceptions of discharge staff about the factors contributing to the delays were gathered through in‐depth interviews and analysed using constant comparative analysis. Findings indicated that HRDD for working aged adults accounted for 11.6% of total mental health bed days in 2018, costing the health system $4, 054, 149. When extrapolated nationally HRDD could cost Australia $269.5 million per year. While individual characteristics and contexts were thought to make some patients more vulnerable, data indicated that the major contributors were lack of housing options, lack of services, difficulty with funding and lack of clear pathways to achieve housing. The findings highlight the urgent need for additional housing for people with mental health issues and a whole of government approach to addressing the substantial issue of housing‐related delayed discharge.